Concurrent measurement of cellular turbidity and hemoglobin to evaluate the antioxidant activity of plants. (1st January 2016) - Bellik, Yuva; Iguer-Ouada, Mokrane
Highlights: Erythrocyte and hemoglobin were measured simultaneously under antioxidant and oxidative conditions. Erythrocyte and hemoglobin were higher in samples treated with ginger extracts. High values of hemoglobin might indicate protection from degradation rather than the lysis of erythrocytes when working with antioxidants. Abstract: In past decades, a multitude of analytical methods for measuring antioxidant activity of plant extracts has been developed. However, when using methods to determine hemoglobin released from human erythrocytes treated with ginger extracts, we found hemoglobin concentrations were significantly higher than in untreated control samples. This suggests in the presence of antioxidants that measuring hemoglobin alone is not sufficient to determine hemolysis. We show concurrent measurement of erythrocyte concentration and hemoglobin is essential in such assays, and describe a new protocol based on simultaneous measurement of cellular turbidity and hemoglobin.